Genetic architecture for yield and its components in castor (Ricinus communis L.): GENETIC ARCHITECTURE FOR YIELD AND ITS COMPONENTS IN CASTOR (RICINUS COMMUNIS L.) - K K PATEL,; HARSHAL E PATIL, (Journal of Oilseeds Research, 2014)
The genetic analysis was done through line x tester design involving five pistillate lines and 13 pollen parents for the development of a set of 65 hybrids in castor, Ricinus communis. The combining ability analysis for yield and its components revealed that both the components, additive and non-additive of genetic variances were significantly influenced by environment. The preponderance of additive gene action was observed for the control of days to 50% flowering and days to 50% maturity of main raceme as well as number of nodes up to main raceme. For the characters plant height and oil content, non-additive gene effect was propounded. The parents SKP-8, 103745, 1379, SKP-93, TMV-5, Aruna, SH-72 and SK2-8A were good general combiners for imparting earliness, former three as well as VP-1 were good general combiner for short plant stature, whereas later two and SKP-82, JH-128, SH-41 and48-1 were good general combiners for oil content. The estimates of gca effects suggested that parents SKP-93, SKP-82, 48-1, Aruna, SPS-35-9B, JI-77 and JH-128 were good general combiners for seed yield and at least for two important yield attributes viz., 100-seed weight, effective branches/plant, number of capsules in main raceme and length of main raceme. The good specific cross combinations for yield were SKP-8 x TMV-5, VP-l x SKI-41 and SKP 25 x 1379, also identified as superior hybrid for earliness, high oil content and short plant stature, respectively. Hence, these may be exploited for commercial cultivation. The hybrids SKP-8 x TMV-5, SKP-25 x JH-128 and SKP-82 x 48-1 depicted significant positive sca effect for seed yield, these hybrids could be exploitedfor development of hybrids and new inbred as well as pistilate lines in castor. The potence ratio of genetic variance suggested preponderance of non-additive gene effect for inheritance of the seed yield/plant, number of capsules in main raceme and number of effective branches.